The Effectiveness of Simulation Game Based Group Counseling in Enhancing Students’ Emotional Regulation - Aldea Putri Rahmawati; Siti Fitriana; Padmi Dhyah Yulianti (ILIN Institute Makassar, 2026)
This study focuses on examining the effectiveness of group counseling services utilizing simulation game techniques in managing the emotions of tenth-grade students at SMA Negeri 1 Mranggen. The intervention consisted of group counseling sessions employing simulation games, conducted over five meetings with a duration of 40 minutes per session. The measured indicators included self-awareness, self-regulation, motivation, empathy, and social skills. Methodologically, this study employed a quantitative approach with a one-group pretest-posttest experimental design. 10 students were selected as subjects through simple random sampling, utilizing a 29-item Likert scale instrument that had been tested for validity and reliability. Based on the results of the t-test, there was an increase in scores for each participant as well as across all emotional management indicators, indicating a significant difference between conditions before and after the intervention.